Perfil clínico, alimentar e estado redox em indivíduos com excesso de peso em Sinop/MT - Jesus, Ezineide de (2023)
The nutritional transition process contributes to an increased risk of obesity developing and associated chronic diseases, which is a public health problem worldwide. Clinical and experimental evidences show a relationship between obesity, dietary profile and redox status. Therefore, we aimed to evaluate the clinical and dietary profiles and redox status of a sample of overweight individuals in Sinop/MT. This is a descriptive and cross-sectional study with a convenience sample of Brazilian adult individuals of both sexes, conducted in a Basic Health Unit in the city of Sinop/MT. Participants were divided according to the body mass index (BMI) into eutrophic (n=5; BMI entre 18,5 e 24,9 kg/m²) and overweight (n=12; BMI ≥25 kg/m²) groups. Clinical parameters (arm, waist and hip circumferences, waist-hip ratio, age, height, weight, and systolic and diastolic blood pressure), metabolic and inflammatory indicators in the blood (AST, ALT, gama GT, fasting glucose, urea, creatinine, total and fractionated cholesterol, triglycerides and PCR), redox status markers (SOD, CAT, GSH, GST, Vit C, TBARS and PCarb) and food intake (carbohydrates, meat and eggs, fruit and natural juice, vegetables, dairy products, industrialized beverages, sweets and fatty preparations) were analyzed. Seventy percent of participants were overweight and 82% had an elevated waist circumference. Regarding metabolic data, there was a trend of increased fasting glucose and triglycerides and decreased HDL levels as body weight increases. Furthermore, there was a positive linear correlation between BMI and triglycerides, also between BMI and glucose reinforcing the trend of higher plasma levels according to increase BMI. It was not possible to demonstrate a significant difference for redox status markers, and there was no significant linear correlation between BMI and these markers. The overweight group reported a lower industrialized beverages and sweets intake, but there was no difference to the other food variables. Therefore, we conclude that most individuals were overweight, which was associated to comorbidities, regardless dietary intake, but age being associated factor. Furthermore, overweight did not modulate redox status.